Pengaruh Kepribadian terhadap Kerjasama Tim dan Dampaknya terhadap Kinerja Karyawan - Wahyu Kusuma Pratiwi; Dwiarko Nugrohoseno (Universitas Negeri Surabaya, 2018)
Human resource management system is the key to success right company to achieve its objectives. It required human resources who are competent for the performance of the resulting increase in accordance with the target company. To improve the performance of the employee, then the company must pay attention to the factors that can affect performance, such as personality and teamwork. This study use a quantitative approach. Type of research is causal research with personality variables and teamwork as the independent variable and performance as the dependent variable. The technique of sampling using a stratified random sampling with a sample of 51 permanent employees Production Department PT Apie Indo Karunia Sidoarjo and using software SMARTPLS 2.0 M3. The results showed theres positive and significant effect of extraversion, agreeableness, conscientiousness, openness to experience variables on teamwork. Theres positive and significant effect of the variable teamwork on employee performance.